Auditory memory and neuropsychological performance in elderly patients - Infantes, Igor (2015)
Objective: To determine the relationship between auditory memory and neuropsychological performance in elderly patients treated at the Geriatric and Gerontology Center of FAP. Design: The research is applied type, while the design is retrospective observational and cross-sectional, with a descriptive correlational level. Institution: Geriatric and Gerontology Center of the Air Force of Peru. Material: Medical records of patients seen in the outpatient Department of Neuropsychology. Methods: 212 clinics between 2012 and 2014 stories were assessed by stratified random sampling. Main outcome measures: Auditory memory and neuropsychological performance in patients older. Results: Patients with Alzheimer’s dementia showed a mean score of 5.17 auditory memory; with vascular dementia, 6.75; with mixed dementia, 4.93; and healthy, 10.05 patients. Conclusions: There is a positive relationship between auditory memory and neuropsychological performance in elderly patients treated at the Geriatric and Gerontology Center of FAP. We also found significant differences in total scores on auditory memory, according to the diagnosis of dementia in patients of the investigated sample.